2016
DOI: 10.1039/c5fo00681c
|View full text |Cite
|
Sign up to set email alerts
|

Induction of ROS-independent DNA damage by curcumin leads to G2/M cell cycle arrest and apoptosis in human papillary thyroid carcinoma BCPAP cells

Abstract: Previously we found that curcumin, the active constituent of dietary spice turmeric, showed potent inhibitory effects on the cell growth of thyroid cancer cells. However, the detailed anti-cancer mechanism of curcumin is still unknown. In this study, we have reported that curcumin induces significant DNA damage in human papillary thyroid carcinoma BCPAP cells in a dose-dependent manner as evidenced by the upregulated phosphorylation of H2A.X at Ser139, which was further confirmed by the long tails in the comet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 32 publications
2
27
0
Order By: Relevance
“…As shown above, SMG potentiated the effect of H 2 O 2 on DNA damage in MES cells, and DNA damage leads to apoptosis (Zhang et al 2016). Previously we observed that SMG itself was unable to induce apoptosis in wild-type MES cells (Li et al 2015).…”
Section: Resultsmentioning
confidence: 80%
“…As shown above, SMG potentiated the effect of H 2 O 2 on DNA damage in MES cells, and DNA damage leads to apoptosis (Zhang et al 2016). Previously we observed that SMG itself was unable to induce apoptosis in wild-type MES cells (Li et al 2015).…”
Section: Resultsmentioning
confidence: 80%
“…Oxidative stress plays an important role in controlling cancer cell behavior, and high levels of ROS increase cancer cell apoptosis [14, 15]. We examined whether increased ROS was required for reduced cell viability and increased apoptosis of LoVo and HT-29 cells with curcumin and/or irinotecan treatment.…”
Section: Resultsmentioning
confidence: 99%
“… 2015 ) and curcumin (Zhang et al. 2016 ), have shown anticancer potential through mitochondrial mechanisms whether associated or otherwise to oxidative stress.…”
Section: Discussionmentioning
confidence: 99%